RAMMED EARTH WALL - GREEN CONSTRUCTION (Global Journal of Advanced Engineering Technologies and Sciences, 2017)
As the building industry quickly changes and demand is shifting towards energy efficient, healthy building that consumes less precious resources. Buildings are a major energy consuming sector in the economy. About 35 to 40% of total energy is consumed by buildings during construction. The major consumption of energy in buildings is during construction and later on for lightening, heating/cooling or air-conditioning systems, This consumption must be minimized. The paper attempts to discuss about the highlights of the green building- a focus on rammed earth wall can be built from local material. Rammed Earth wall is used as insulation on the face of exterior wall for heating/ cooling purpose of the buildings it may release the temperature slowly. Rammed Earth wall is a method of insulating of building in hot and cold climate regions, in this paper applicability of rammed earth wall is studied in colder climate region like Afghanistan – Bamyan province, there is very cold in the winter almost -20C. Rammed earth wall is made of local material can be used as an insulation to conserve Energy (consumed for heating purpose of the building) or indoor building temperature. At this stage attempt to achieve comparison of cost/time between rammed earth wall and conventional materials. Water ratio analysis need to be carried out to finding out proper water ratio and proper moisture of earth before placing in the framework to be compacted well. Once rammed earth wall build it should be used for 4-5 decades and the main objective of compressive testing to find the ultimate crushing strength of rammed earth wall, which is carried out in Afghanistan.